2007
DOI: 10.1016/j.diabres.2007.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Gestational diabetes and the incidence of diabetes in the 5 years following the index pregnancy in South Indian women

Abstract: This study was carried out to examine the incidence of diabetes and the factors associated with this in a cohort of South Indian women 5 years after they were examined for gestational diabetes (GDM). Women (N = 630) whose GDM status was determined (Carpenter-Coustan criteria; GDM: N = 41) delivered live babies without major anomalies at the Holdsworth Memorial Hospital, Mysore. Of these, 526 women (GDM: N = 35) available for follow-up after 5 years underwent a 2-h oral glucose tolerance test and detailed anthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
43
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 25 publications
5
43
2
1
Order By: Relevance
“…We observed an overall prevalence of 32.25% for diabetes, at median period of 14 months of postpartum screening. The incidence of was nearly 50% when the mean follow up period exceeded 2years, which is much former than those reported by other Indian studies (35%-50%, at mean follow up of 5 years) [4][5][6] . The occurrence of diabetes in our study group is as well greatly elevated than has been published in general population studies.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…We observed an overall prevalence of 32.25% for diabetes, at median period of 14 months of postpartum screening. The incidence of was nearly 50% when the mean follow up period exceeded 2years, which is much former than those reported by other Indian studies (35%-50%, at mean follow up of 5 years) [4][5][6] . The occurrence of diabetes in our study group is as well greatly elevated than has been published in general population studies.…”
Section: Discussioncontrasting
confidence: 38%
“…Whereas greater incidence of both T2DM and GMD are reported in India [2,3] . At present there is inadequate information available about the progression of T2DM in women with earlier GDM [4][5][6] . The American Diabetes Association (ADA) guidelines state that women with GDM ought to undergo screening for continual diabetes at 6-12 weeks postpartum, by means of the 2 hour OGTT [7] .…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that women with GDM had defects in both insulin sensitivity and insulin secretion (25). In one study, women with GDM were found to be more insulin resistant, and also had lower insulin increment at the index pregnancy compared non-GDM women (26). In another study, women with previous GDM and control subjects were found to differ only in insulin secretion at postpartum follow-up, which was associated with the difference in the rate of fasting hyperglycemia (21).…”
Section: Discussionmentioning
confidence: 98%
“…It should be noted that the GDM mothers are also at risk of developing another GDM during subsequent pregnancies with a probability of 30 to 84% (Kim et al 2007;Reece et al 2009). These mothers are predisposed to develop metabolic syndrome by 60% (Krishnaveni et al 2007) or type 2 diabetes with an incidence of 37%. The prevalence of GDM is 3.5 times higher in these women than those in a normal pregnancy (Lee et al 2008).…”
Section: Introductionmentioning
confidence: 99%